Anemia is associated with severe illness in COVID‐19: A retrospective cohort study. Issue 3 (10th November 2020) - Tao, Zheying; Xu, Jing; Chen, Wei; Yang, Zhitao; Xu, Xiaoman; Liu, Ling; Chen, Ruwu; Xie, Jingyuan; Liu, Mingyu; Wu, Jingyi; Wang, Huiming; Liu, Jialin
Abstract: Anemia commonly aggravates the severity of respiratory diseases, whereas thus far, few studies have elucidated the impact of anemia on coronavirus disease 2019 (COVID‐19). The aim of this study was to evaluate the clinical characteristics of patients with anemia, and to further explore the relationship between anemia and the severity of COVID‐19. In this single‐center, retrospective, observational study, a total of 222 confirmed patients admitted to Wuhan Ninth Hospital from 1 December 2019 to 20 March 2020 were recruited, including 79 patients with anemia and 143 patients without anemia. Clinical characteristics, laboratory findings, disease progression and prognosis were collected and analyzed. Risk factors associated with the severe illness in COVID‐19 were established by univariable and multivariable logistic regression models. In our cohort, compared to patients without anemia, patients with anemia were more likely to have one or more comorbidities and severe COVID‐19 illness. More patients demonstrated elevated levels of C‐reactive protein (CRP), procalcitonin (PCT) and creatinine in anemia group. Levels of erythrocyte sedimentation rate, D‐dimer, myoglobin, T‐pro brain natriuretic peptide (T‐pro‐BNP) and urea nitrogen in patients with anemia were significantly higher than those without. In addition, the proportion of patients with dyspnea, elevated CRP, and PCT was positively associated with the severity of anemia. The odd ratio of anemia related to the severe condition of COVID‐19 was 3.47 (95% confidence interval [CI]: 1.02‐11.75; P  = .046) and 3.77 (95% CI: 1.33‐10.71; P  = .013) after adjustment for baseline date and laboratory indices, respectively. Anemia is an independent risk factor associated with the severe illness of COVID‐19, and healthcare professionals should be more sensitive to the hemoglobin levels of COVID‐19 patients on admission. Awareness of anemia as a risk factor for COVID‐19 was of great significance. Highlights: Anemia is an independent risk factor associated with the severe illness of COVID‐19. Covid‐19 patients with anemia exhibit severe inflammation response, which is positively associated with the severity of anemia. Covid‐19 patients with anemia are older and exhibit severe organ injuries including poorer lung function, more serious myocardial injury and renal dysfunction.